2012
DOI: 10.1245/s10434-012-2519-8
|View full text |Cite
|
Sign up to set email alerts
|

The E2F Transcription Factor 1 Transactives Stathmin 1 in Hepatocellular Carcinoma

Abstract: Upregulation of E2F1 and STMN1 proteins associate with worse outcomes in patients with HCC. E2F1 significantly correlates with STMN1 protein level in HCC lesions and in vitro transactivation assays, suggesting that STMN1 gene is transactivated by the E2F1 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…As a ubiquitous microtubule destabilizing protein, STMN1 is an important key in preventing microtubule polymerization and promoting microtubule catastrophe in interphase and late mitosis [7]. STMN1 is overexpressed across many different human cancers such as Merkel cell carcinomas of the skin [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitous microtubule destabilizing protein, STMN1 is an important key in preventing microtubule polymerization and promoting microtubule catastrophe in interphase and late mitosis [7]. STMN1 is overexpressed across many different human cancers such as Merkel cell carcinomas of the skin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have revealed an oncogenic role of STMN1 based on its expression profiles in patients or effects of manipulating its expression on cellular tumorigenicity394046. Silencing of STMN1 expression in the HCC cell line, HCCLM3, was shown to significantly reduce cell proliferation, adhesion and invasion, and trigger apoptosis40.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of STMN1 expression in the HCC cell line, HCCLM3, was shown to significantly reduce cell proliferation, adhesion and invasion, and trigger apoptosis40. Exogenous expression of E2F1 and the transcription factor DP-1 (TFDP1) has been shown to induce STMN1 mRNA expression46. Moreover, overexpression of STMN1 results in microtubule disassembly and is associated with formation of binucleated cells39.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the overexpression of op18 in HCC cells decreased their sensitivity, whereas small interfering RNAs targeting op18 enhanced their sensitivity to GA, suggesting that op18 is a potentially significant target for GA in combating HCC. Results of a study by Chen et al (13) revealed that the upregulation of E2F1 and op18 proteins is associated with worse outcomes in patients with HCC, and E2F1 significantly correlates with the op18 protein level in HCC lesions and in vitro transactivation assays. It was reported that op18 expression may be associated with HCC metastasis, recurrence and prognosis, by detecting op18 mRNA expression in normal liver, non-metastasis, metastasis and recurrence in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the association between the expression of op18 and HCC (12)(13)(14). Wang et al (12) found that op18 distinctly expressed proteins identified in HCC cells treated by gambogic acid (GA) by proteomic approach and western blotting.…”
Section: Discussionmentioning
confidence: 99%